Assessing Cohabitation from the Perspective of Living Law, the Criminal Code and the National Criminal Code - Kartono, Kartono; Suhendar, Suhendar (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Cohabitation living together as husband and wife without being officially married is a social phenomenon that is increasingly common in Indonesia. This phenomenon raises various pros and cons, especially from a legal and moral perspective. The aim of this research is to analyze the perspective of living law, the Criminal Code and the national Criminal Code. This research uses normative juridical research methods. The data collection technique used in this research is literature study. The data analysis technique used in this research is qualitative data analysis. The research results show that from a living law perspective in several areas, cohabitation is considered a normal practice and does not need to be punished. On the other hand, cohabitation is also seen as an act that violates norms and customs in several other regions. Meanwhile, from the perspective of the old Criminal Code, living together was not strictly regulated, but there were several articles that could be linked to behavior that was considered to violate moral norms. Meanwhile, the National Criminal Code brings several important changes, one of which is more detailed living arrangements. This reflects a stricter legal approach to cohabitation, potentially providing criminal sanctions for behavior that was not previously explicitly regulated.